The Effects of Facial Attractiveness and Familiarity on Facial Expression Recognition - Li, Jinhui; He, Dexian; Zhou, Lingdan; Zhao, Xueru; Zhao, Tingting; Zhang, Wei; He, Xianyou (Frontiers in Psychology, 2019)
The classic theory of face perception holds that the invariant (e.g., identity and race) and variant (e.g., expression) dimensions of face information are independent of one another. Two separate neural systems are involved in face processing. However, the dynamic theory of face perception indicates that these two neural systems interact bidirectionally. Accordingly, by using the emotion categorization task and morph movies task, we investigated the influence of facial attractiveness on facial expression recognition and provided further evidence supporting the dynamic theory of face perception in both the static and dynamic contexts. In addition, this research used familiar celebrities (including actors, television personalities, politicians, and comedians) and explored the role of familiarity in face perception. In two experiments, the participants were asked to assess the expressions of faces with different levels of attractiveness and different levels of familiarity. We found that regardless of being in a static or dynamic face situation, happy expressions on attractive faces can be recognized more quickly, highlighting the advantage of happy expression recognition. Moreover, in static and dynamic familiar face situations, familiarity has a greater impact on expression recognition, and the influence of attraction on expression recognition may be weakened or even unaffected. Our results show that facial attractiveness influences the recognition of facial expressions in both static and dynamic contexts and highlight the importance of familiarity in face perception.